HUBUNGAN EKSPRESI PROTEIN HYPOXIA-INDUCIBLE FACTOR-1α DENGAN STADIUM KLINIS PADA KARSINOMA SEL SKUAMOSA GLOTIS - PRIYANTO, PRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Background: Laryngeal squamous cell carcinoma is one of most important malignancy in head and neck. This malignancy mostly found in glottis area, about 70% of laryngeal malignancy. HIF-1α is a protein commonly found in solid tumour and plays a crucial role in biological processes under hypoxic conditions especially angiogenesis and carcinogenesis. Aim: This study examine the association between HIF-1α expression levels and clinical stage in glottic squamous cell carcinoma. Methode: This cross sectional study examine the association between HIF-1α expression levels and clinical stage in glottis squamous cell carcinoma. Total 42 paraffin tissue blocks from glottic squamous cell carcinoma patients in pathological department of Dr. Sardjito hospital were examined immunohistochemically to see the expression of HIF-1α using anti HIF-1α monoclonal antibody. Association between HIF-1α expression levels and clinical stage were analysed using chi square test. Result: In Total 42 paraffin tissue blocks from glottic squamous cell carcinoma patients, we found 38 patients in advanced stage (25 positively expressed HIF-1α; 13 negatively expressed HIF-1α) and 4 patients in early stage (2 positively expressed HIF-1α; 2 negatively expressed HIF-1α). From the analysis we found no statistically significant association between HIF-1α protein expression and clinical stage in glottic squamous cell carcinoma (p > 0,05; p = 0,451). Conclusion: There is no statistically significant association between HIF-1α protein expression and clinical stage in glottic squamous cell carcinoma. Keywords: Glottic squamous cell carcinoma, hypoxia inducible factor-1α, immunohistochemical, clinical stage, association